KELAYAKAN MEDIA FLICHART KEANEKARAGAMAN JAMUR KALIMANTAN BARAT SUBMATERI PENGELOMPOKAN JAMUR KELAS X SMA - Sapardi Sapardi (FKIP Universitas Tanjungpura, 2021)
This study aims to describe the feasibility of flipchart media about mushroom diversity in West Kalimantan from the results of several studies in the Biology Education study program in mushroom grouping submersion in class X SMA and describe the development of mushroom diversity flipchart media in West Kalimantan for learning mushroom grouping submersion in class X SMA . The form of research used is to provide an overview of the results of several studies that have been carried out in the Biology Education Study Program FKIP Untan on mushroom diversity in West Kalimantan, which is implemented in flipchart media. Flipchart media were tested by experts, namely two lecturers in Biology FKIP Untan and three biology class X high school teachers. The selected biology teachers are SMA Negeri 1 Sungai Raya, SMA Negeri 2 Sungai Raya and SMA Santun Untan. Based on the validator's evaluation, the flipchart is included in the valid category with an average total validation of 3.6 and is feasible/ can be used as a learning medium in the mushroom grouping class X submersion. KEY WORDS: Feasibility, Flipchart, Mushroom Grouping